Integrasi Nilai-Nilai Islam dalam Pembelajaran Matematika SD/MI - Mimi Hariyani (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2013)
Nowadays, learning mathematics is still separated with Islamic religious education. Yet at the latest in madrasah curricu-lum requires the integration of Islamic values ​​in each subject. Integration of Islamic values ​​in the learning of mathematics itself is often considered difficult because teachers have not been accustomed to apply it. Actually, integrating Islamic values ​​into learning math is not difficult, it can be done in various ways such as: always mention the name of Allah, the use of the term, visual illustrations, or examples of applications, insert the relevant verse or hadith, search history, network topics, symbols kauniah verses